HIGH VALUE OF BIOACTIVE COMPOUNDS FROM CORIANDRUM SATIVUM L FOR MULTIPLE BIOTHERAPEUTIC APPLICATIONS - Norma M. De la Fuente-Salcido; David Francisco Lafuente-Rincón (Universal Journal of Pharmaceutical Research, 2025)
Currently, people demanding nutrient-rich food products that provide additional health benefits. In this sense, Coriandrum sativum L, the most consumed spice around the world increasing its popularity due to its high nutritional value and confirmed pharmacological effects. Bioactive compounds derived from coriander have a wide variety of medical and biotherapeutic applications that extend beyond their well-established gastronomic relevance. Here, the information currently available on the presence, diversity, and extraction methods of the main components of coriander are reviewed. The multiple benefits of include cilantro in the diet and its effect on the treatment of global impact chronic diseases of such as cancer, heart disease, Alzheimer's disease, diabetes, kidney disease, cerebrovascular diseases, among others, are also highlighted. Likewise, the primary biological activities of coriander are detailed, such as antioxidant capacity and antimicrobial activity derived from specific phytochemicals. This update shows the composition and describe the mixture of bioactive constituents included in the herbaceous plant and/or extracts, emphasizing the biological functions mainly as antimicrobial agents and its confirmed antioxidant function. Coriander is a reservoir of bioactivities combined, with promising potential to use and/or increase health and promote well-being. Peer Review History: Received 6 December 2024; Reviewed 9 January 2025; Accepted 17 February; Available online 15 March 2025 Academic Editor: Dr. Iman Muhammad Higazy , National Research Center, Egypt, imane.higazy@hotmail.com Reviewers: Dr. Omonkhelin J Owolabi, University of Benin, Nigeria, owolabi@uniben.edu Dr. Omid Gholami, Sabzevar University of Medical Sciences, Iran, omidghphd@gmail.com